a) 3[2(x + 4) - 3(x - 5)] = 4[3(x + 2) - 4(x + 1)] + 15;
b) 3[8 - 5(3r-2)] + 4(4x - 9) = 2[3(2x - 5) + 28] - 49;
c) 2[7(2-1)-3(4r - 1)] = 3[5(3x + 2) - 1]-(19x + 13);
d) 3[11(x + 2) - 2(2 - 5.x)] = 2[8(3 + 4x) + 5] - (6x + 11).
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
a)
3[2×+8 -3×+15]=4[3×+6-4×-4]+15
6×+24-9×+45=12×+24-16×-16+15
6×-9×-12×+16×=24-16+15-24-45
-3×-12×+16×=8+15-24-45
-15×+16×=23-24-45
1×=44
×=44
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Informatică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă